Increasing The Original Tax Districts: Case of Local Regulation no. 02/2012 on Wall Painting Tax in Metro Regency - Yeni Ika Widayanti (Saburai International Journal of Social Sciences and Development, 2017)
The development of the number of wall painting in Metro City cannot be separated from the behavior of people who tend to let it happen without seeing the consequences. The change of behavior of this society because of the tendency to have an economic motive without noticing that the wall painting made around the building of their house was actually disrupt the beauty of the surrounding environment and the urban environment in general. The enactment of regional regulation No. 02 of 2012 on local taxes there will be a tax burden per year whose value is adjusted by the extent of the wall painting. The problem is whether there is no more leakage in local tax revenue (PAD) next? It is caused of in general the attainment of PAD is not maximal due to indications of leaks in some items. A number of factions of every plenary in the DPRD, always proposed the formation of special committee of local revenue. This is based on the target and realization of local revenue (PAD) Metro city has not maximum year to year. There are indications of leaks in parking sector items, billboards, and restaurants, expected to be scaled down. At least with the information of Pansus PAD then the transparency of PAD that occurs and share the barriers that occur can be found the solution. Necessary moral awareness for the apparatus of the teachings of urban government agencies Metro the importance of moral awareness in carrying out the task, so that no more unwanted things happen such as: misuse of advertisement tax revenue, parking tax and restaurant tax, and the hotel entered the pockets of bank accounts elements of government apparatus. So that the efforts of Dispenda Metro City in raising the original revenue area can run with the maximum as expected.